Consumption frequency of junk food, simple carbohydrate intake, and total cholesterol levels in Esa Unggul University employees: Frekuensi konsumsi junk food, asupan karbohidrat sederhana dan kadar kolesterol total pada karyawan Universitas Esa Unggul - Lestari, Nurindah; Sitoayu, Laras; Nadiyah, Nadiyah; Dewanti, Lintang Purwara; Wahyuni, Yulia; Sumitra, Putri Azahra (Utan Kayu Publishing, 2023)
This study aims to determine the relationship of the frequency of consuming junk food, intake of simple carbohydrates, physical activity and total cholesterol levels in Esa Unggul University employees. This type of research is observational with cross sectional research design. The total population of 400 respondents obtained the number of samples using stratified random sampling is as many as 60 respondents selected with respondents ranging from age 27-61 years. Data collected are frequency of consuming junk food using food frequency (FFQ) instruments for the past 1 month, physical activity using 2x24 hour Physical Activity Level (PAL) instrument form, simple carbohydrate intake using 2x24 hour food recall instrument and total cholesterol level using instrument check instrument digital cholesterol. Data analysis in this study used the Pearson correlation test. Average junk food consumption with a score (95.7 ± 64.96), physical activity (1.67 ± 0.21), intake of simple carbohydrates (77.64 ± 32.91) grams and total cholesterol levels (184, 7 ± 36.25) ml / dl. There was a relationship between consuming junk food (P = 0.0001; r = 0.454), intake of simple carbohydrates (P = 0.006; r = 0.349) and total cholesterol levels. However, there was no relationship between physical activity and total cholesterol levels (P = 0.167; r = -0.181). Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan frekuensi mengonsumsi junk food, asupan karbohidrat sederhana, aktivitas fisik dan kadar kolesterol total pada karyawan Universitas Esa Unggul. Jenis penelitian ini bersifat observasional dengan desain penelitian cross sectional. Jumlah populasi 400 responden didapatkan jumlah sampel dengan menggunakan cara stratified random sampling adalah sebanyak 60 responden yang terpilih dengan responden mulai dari usia 27–61 tahun. Data yang dikumpulkan yaitu frekuensi mengonsumsi junk food menggunakan instrumen food frequency (FFQ) 1 bulan terakhir, aktivitas fisik menggunakan instrumen form Physical Activity Level (PAL) 2x24 jam, asupan karbohidrat sederhana menggunakan instrumen food recall 2x24 jam dan kadar kolesterol total menggunakan intrumen alat cek kolesterol digital. Analisis data pada penelitian ini menggunakan uji korelasi pearson. Rata-rata mengonsumsi junk food dengan skor (95,7 ± 64,96), aktivitas fisik (1,67 ± 0,21), asupan karbohidrat sederhana (77,64 ± 32,91) gram dan kadar kolesterol total (184,7 ± 36,25) ml/dl. Terdapat hubungan antara mengonsumsi junk food (P=0,0001; r=0,454), asupan karbohidrat sederhana (P=0,006; r=0,349) dan kadar kolesterol total. Namun, tidak ada hubungan antara aktivitas fisik dan kadar kolesterol total (P=0,167; r=-0,181).